Argumentation Skills of Pre-Service Physics Teachers: An Exploration During a STEM Project in Water Turbidity - Nuryadin, Atin; Wisutama*, Remanda Arya; Sulaeman, Nurul Fitriyah; Subagiyo, Lambang; Marzan, Joey-Nell T. (Jurnal Pendidikan Sains Indonesia, 2024)
Pre-service physics teachers (PSPTs) should have an established argumentation skill, a recognized skill in 21st-century education, to support learning. In line with this, the study explored the argumentation skills of PSPTs using an argumentation framework, Toulmins argument pattern (TAP), to provide a clear view of the argumentation skills of the 39 PSPTs who were involved in a four-meeting science, technology, engineering, and mathematics (STEM) project. The study employed a mixed method research design in which the quantitative portion investigated the categories of TAP aspects, and the qualitative portion focused on exploring the argumentation patterns of the PSPTs. The data for this study was derived from the STEM project worksheets answered by the pre-service teachers. Quantitative analysis revealed PSPTs' argumentation aspect to be high regarding the claim aspect (97.44%) and data aspect (94.87%). Meanwhile, the warrant aspect (53.85%) is moderate, backing (20.51%) is low, and the rebuttal aspect (2.56%) is deficient. On the other hand, the qualitative analysis showed that PSPTs make four argumentation patterns: claim data (C-D); claim, data warrant (C-D-W); claim, data, warrant, backing (C-D-W-B); and claim, data, rebuttal (C-D-R). Considering TAP, quantitative and qualitative findings imply that PSPTs' argumentation skills still need to be developed, particularly on low-level aspects and in constructing a solid argument following the claim, data, warrant, backing, and rebuttal pattern